Seminal apoptosis and serum levels of CB153 and DDE in European and Inuit populations - Stronati A; Bizzaro D; Cecati M; Bordicchia M; Ferrante L; Spano M; Toft G; Bonde JP; Hagmar L; Jonsson B; Rignell Hydbom A; Rylander L; et al. (2006)
.